A study on the validity of the tourism-led growth hypothesis in the Philippines - FERNANDEZ, FRANCINE CLAIRE (Archīum Ateneo, 2017)
This paper explored the validity of the Tourism-Led Growth Hypothesis in the Philippine context. It utilized a theoretical model developed by Feder (1982) as well as an empirical model developed by Corts-Jimnez and Pulina (2009), with some modifications from the researcher. The Johansen Test for Cointegration was used to verify the existence of cointegrating vectors in the model, while the Vector Error Correction Model (VECM) was used to determine the directionality of the Granger causal relationship among the variables. The results of the tests verified the existence of a unidirectional Granger causal relationship running from tourism activity, physical capital and human capital to economic growth, confirming the validity of the Tourism-Led Growth Hypothesis within the Philippine context.